The Influence Of Social Presence, Physical Presence, And Trust On Impulsive Buying Behavior In Tiktok Live Users In Java Island - Shafa Tasya Salsabila; Yuli Kartika Dewi (UNIVED Press, 2024)
This research is a quantitative research that intends to determine the positive influence of social presence, physical presence, and trust separately on impulsive buying in TikTok Live users. Non-probability sampling technique with purposive sampling approach was used on 189 respondents with certain criteria, namely domiciled in Java, age range 18-34 years, and have shopped online through TikTok Live. Data collection techniques through Google Form questionnaires use Likert scale and processed using SPSS 27.The results showed that (1) Social presence (Sig = 0,001) had a significantly positive influence on the impulsive buying of TikTok Live users, (2) Physical presence (Sig = 0,025) had a significantly positive influence on the impulsive buying of TikTok Live users, and (3) Trust (Sig = 0.028) has a significantly positive influence on the impulsive buying of TikTok Live users. Technology in today's era has developed rapidly, making life more practical, because everything can be done through social media. With the application of technology, digital marketing has taken a leading role in all areas of marketing, creating an attractive landscape and atmosphere for customers, particularly in the field of social media networks, particularly TikTok Live.